Vibration Level Improvement of Id Fan in a Cement Plant Based On CFD Study of Incoming Dust Particles Streamline - Darmanto, Prihadi Setyo; Syahlan, Arief; Amalia, Alfi (Transactions on Engineering and Computing Sciences, 2016)
This paper presents numerical study of aerosol flow inside of the induce draft (ID) fan inlet duct of a cement plant and the field observation of the proposed guide plate implementation as vibration reducer. Since ID fan sucks the flow from the outlet of cyclone separator, that is normally swirling flow, and the geometry of the duct tends to produce unbalance fine particles distribution over the duct cross section, the vibration of ID fan increases periodically due to unbalance built-up of the fine particles over fan blades surface. Numerical result shows that, at the ID fan inlet, the distribution of fine particles is unbalance. The ratio of particles concentration in the gas entering fan side and motor side of the ID fan is 1.4 to 1 which influences on the unbalance deposition of sticky particles over related blades surface. Using proper guide plate installed in the last duct elbow before entering to the fan, the ratio of unbalance fine particles concentration reduces to 1.05 to 1 and is kept up to the fan free side and motor side inlets. The proposed guide plate has also already installed in a cement plant ID fan duct and vibration characteristic was also observed during 4 months after tie-in period. The plant vibration observation shows that its level is practically unchanged and maintained at low level (around 2 mm/s at fan side and 0.5 mm/s at motor side) which is still lower than maximum limit (11 mm/s). This condition reduces significantly vibration level and eliminates practically plant stop due to over vibration of ID fan along last 4 months operation which was normally suffered every 1.5 months before implementation of this study.